2021
DOI: 10.5334/gh.858
|View full text |Cite
|
Sign up to set email alerts
|

Association between Blood Pressure and HIV Status in Rural Uganda: Results of Cross-Sectional Analysis

Abstract: Introduction: The association between HIV status and hypertension is not well described within sub-Saharan Africa. We examined prevalence and risk factors for hypertension among HIV positive and negative individuals living in a rural district of Uganda. Methods: We conducted a cross-sectional analysis in two concurrent cohorts of 600 HIV negative and 721 HIV seropositive individuals aged ≥35 years. Results: Of the 721 HIV positive participants, 59.8% were women and the median age was 44.3 years, while for HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
3
3
0
Order By: Relevance
“…In this study, the sample included more females (69%) than males. This finding is similar to past studies conducted in sub-Saharan Africa, including Tanzania with 67.2% (Njelekela et al, 2016), Uganda 59.8% (Niwaha et al, 2021), and Nigeria 60.3% (Ekrikpo et al, 2018). The reason for more females could be a higher likelihood of engaging in care with the health system than males.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the sample included more females (69%) than males. This finding is similar to past studies conducted in sub-Saharan Africa, including Tanzania with 67.2% (Njelekela et al, 2016), Uganda 59.8% (Niwaha et al, 2021), and Nigeria 60.3% (Ekrikpo et al, 2018). The reason for more females could be a higher likelihood of engaging in care with the health system than males.…”
Section: Discussionsupporting
confidence: 91%
“…We found duration on ART not to be associated with hypertension in our study. A study conducted in Uganda reported a similar result (Niwaha et al, 2021). The suboptimal level of adherence might play a role in this finding.…”
Section: Discussionsupporting
confidence: 59%
“…The main finding and key message of our study is the very high prevalence of HTN in PLWH despite their young age (almost 20%), of whom almost half are unaware of their condition. The prevalence of 17.5% in our population is comparable to those reported in Nigeria 29 , Zimbabwe 30 , South Africa 31 Zambia 32 and Tanzania 33 , but lower than those reported in Uganda 34 , Cameroon 35 , Brazil 36 , China 17 , 18 Ugandan rural study 37 and Argentina 38 . Similarly, our findings are higher than those reported in Ethiopia 16,39,40 and Kenya 41 .…”
Section: Discussionsupporting
confidence: 68%
“…Incidentally, peer reviewed studies focussing on blood pressure estimates in PLHIV initiated on ART and untreated HIV negative controls revealed that HIV infection was associated with lower SBP, while treatment was associated with higher lipid levels in Sub-Saharan Africa. 29 , 30 However, this study could not establish the prevalence of hypotension as a major risk factor leading to CVDs among PLHIV initiated on ART, suggesting that future studies measure the association of biomarkers of metabolic risks in the prediction of CVDs at health facility level.…”
Section: Discussionmentioning
confidence: 85%
“…The current findings are contrary to a study conducted by Niwaha et al , who could not find notable differences in the odds of hypertension by CD4 count, viral load, or ART among HIV positive individuals in this sample. 30 At the time of data collection, the majority of the patients (53.67%) were on ART therapy for more than 2 years, specifically on first-line regimens such as TDF+3TC+NVP (38.19%), TDF/FTC/EFV(1F) (14.12%) and TDF/FTC/EFV (8.8%) respectively. However, with the advent of ‘Test and Treat’ in 2019, early diagnosis and targeted management of CVDs among PLHIV initiated on ART were optimised..…”
Section: Discussionmentioning
confidence: 99%